The Socio-Political Context of Holocaust Education in Post-Soviet Russia - Czajkowska, Agata (INSTED: Interdisciplinary Studies in Education & Society, 2021)
The article presents the genesis of Holocaust education in the Russian Federation. Holocaust education in the world is currently monitored by the International Holocaust Remembrance Alliance, which, however, does not take into account the state of Holocaust education in Russia, focusing instead on European countries. The text presents the selected themes of the study on socio-political dimensions of teaching about the Holocaust in the Russian system of formal and non-formal education and attempts to illustrate the "Russian story" of the Holocaust in the face of the dominant ideology.